Optimizing titanium implant performance: Electrophoretic deposition of hydroxyapatite/chitosan/hyaluronic acid coatings - Ningrum, E.O.; Suroto, H.; Suprapto, S.; Azilah, Ajit; Sumaiya, Zainal Abidin; Karisma, A.D.; Hamzah, A.; Mamun, U.Z.; Rosanti, M.S.; Widiyanto, Sigit (Russian Association of Corrosion Engineers, 2024)
Titanium alloy Ti6Al4V is extensively utilized in biomedical implants owing to its advantageous mechanical characteristics and biocompatibility. Nevertheless, the presence of vanadium and aluminum ions may result in cytotoxic effects, allergic reactions, and hindered bone mineralization. To mitigate these concerns, a variety of surface modification techniques have been developed to improve the alloy’s biocompatibility for medical applications. Consequently, this study investigated the efficacy of a composite coating composed of hydroxyapatite, chitosan, and hyaluronic acid to enhance the biocompatibility, corrosion resistance, and antibacterial properties of Ti6Al4V implants. Different formulations of HAp/CS/HA coatings were applied to Ti6Al4V substrates through electrodeposition (40 V, 4 min), chosen for its effectiveness in achieving uniform coatings. The resulting coatings displayed a consistent morphology, and FTIR analysis validated the presence of characteristic functional groups linked to HAp, CS, and HA. The thickness of the coatings was found to be directly related to the concentration of HAp, while the incorporation of HA led to a reduction in thickness due to increased viscosity of the solution. Bioactivity evaluations in Simulated Body Fluid indicated that coatings with elevated HAp content demonstrated enhanced resistance to degradation. Importantly, the HAp/CS/HA coatings significantly improved antibacterial activity against E. coli, with formulations containing higher HAp concentrations showing the lowest corrosion rates. These results underscore the potential of HAp/CS/HA coatings in enhancing the biocompatibility, corrosion resistance, and antibacterial properties of Ti6Al4V implants, thereby improving their performance in biomedical applications.